Vitamin C Helps in the Absorption of Iron in Iron Deficiency Anemia - Restu Krisnanda (Global Health Science Group, 2020)
Anemia is defined as a condition in which the number of red blood cells or the concentration of hemoglobin in the blood is unable to meet the physiological needs of the body. Factors that can cause anemia include parental education level, level of knowledge about anemia, economic level, iron intake, vitamin C intake and the length of the menstrual cycle. The rate of anemia due to iron deficiency in Indonesia reaches 72.3%. Iron is an important microelement for the body. Iron is needed in the process of forming blood in the synthesis of hemoglobin. Hemoglobin functions to bind and deliver oxygen to all parts of the body. Vitamin C is a water soluble vitamin and functions to maintain endurance. In addition, vitamin C also plays a role in helping iron absorption. This writing method is a literature review with sources from books, national and international journals and websites. The number of literature used is 22 and was taken from 1987 to 2017. The results of several studies indicate that vitamin C given with iron will have an impact in the form of increased iron absorption. In conclusion, vitamin C helps in the absorption of iron by converting iron from ferric to ferrous so that it is more easily absorbed by the body.